2012
DOI: 10.22358/jafs/66068/2012
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining farm animal embryos <i>in vitro</i>

Abstract: This paper reviews the basic knowledge about obtaining farm animal embryos in vitro with special focus on differences among species and application of this procedure in the future. In vitro production of farm animal embryos consists of in vitro maturation (IVM) of oocytes, in vitro fertilization (IVF) of matured oocytes, and in vitro culture (IVC) of embryos. Oocytes can be collected from live animals (by laparotomy, laparoscopy, Ovum Pick Up) or from slaughtered ones (by puncture, sectioning). Usually immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 92 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…Embryo transfer (ET) can be used in animal breeding (Duszewska et al, 2012), mainly as a part of a cattle breeding system (Merton et al, 2003). Stádník et al (2013) reported a growing trend of ETs performed worldwide, however, significantly reduced ET cycles have been recorded in the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo transfer (ET) can be used in animal breeding (Duszewska et al, 2012), mainly as a part of a cattle breeding system (Merton et al, 2003). Stádník et al (2013) reported a growing trend of ETs performed worldwide, however, significantly reduced ET cycles have been recorded in the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
“…The last stage IVP is known as in vitro culture. That is the development of the embryos from zygote to the morula and blastocyst stages (Duszewska et al, 2012). According to different authors (Lonergan & Fair, 2008;Paramio, 2010;Dang-Nguyen et al, 2011), this encompasses nuclear and cytoplasmic modifications and their mutual interactions.…”
Section: Principles Of In Vitro Embryo Productionmentioning
confidence: 99%
“…In vitro embryo production (IVEP) is one of the most crucial techniques amongst embryo biotechnologies used in farm animal breeding since it does not only help in production of high genetic merit animals, but also serves as an excellent source of embryos for emerging biotechnologies like embryo sexing, cloning, nuclear transfer and transgenesis (Duszewska et al, 2012;Hafez, 2015). Furthermore, it allows analyzing embryo development potential, including the pattern of gene expression, epigenetic modifications and cytogenetic disorders during the development (Galli & Lazzari, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmes for protection of the Wisent “in situ” and “ex situ” have been implemented in many European countries (http://www.bison-ebcc.eu). A new approach, which allows us to actively protect the Wisent and help its preservation by increasing reproductive potential, is in vitro production of embryos (Duszewska, Rąpała, Trzeciak, Dąbrowski, & Piliszek, ).…”
Section: Introductionmentioning
confidence: 99%